The Teaching of The Song Zapin Imam Berempat in The Form of a Mixed Ensemble In High School 1 Pinggir - Yanda, Martha Febri; Hendri, Yon; Awerman, Awerman; Syaputra, Weldi (Scoring: Journal of Film Music, 2024)
Learning Zapin Imam Berempat in the form of a mixed ensemble in high school N 1 Pinggir. The song is orchestrated using four kinds of instruments, piano, ballet, guitar, and kajon. This research uses the Action Reseach method. In data collection using the Kemmis and Mc Taggart models of a spiral model in which there are Cycles 1 and Cycles II, when the problem is not solved then proceed to the next cycle until the problem has been solved. This research is done through phases, planning, action, observation, and reflection in each cycle. The results of this study show that the pupils in receiving learning are happy. I'm so excited, because this song of Zapin Imam Berempat is easy to accept by pupils. The students gained musical knowledge in particular in the form of an ensemble, so that the students were able to present Zapin Imam Berempat songs in an ensemble form in front of the audience.